JAMI' DARUL MUTAQQIM MOSQUE: ETHNOMATHEMATICS EXPLORATORY - Permatasari, Dian (Department of Mathematics Education , University of Jember, 2022)
The purpose of this research is to explore the concepts contained in the building of the Jami' Darul Mutaqqim Mosque and identify learning resources for ethnomathematics of it according to the subjects, materials, and basic competencies of students based on the Revised 2013 Curriculum. This study uses a qualitative method with an ethnographic approach. Research using ethnography attempts to describe, explain, and analyze all elements of culture that exist in society. This research is collecting data using deep observation and documentation, also analyzing across the curriculum. Based on the results and discussion, it can be concluded that there are ethnomathematical values in the Jami' Darul Mutaqqim Mosque. Ethnomathematics appears in the shape of the parts of the mosque building. The parts of the mosque are 1) the adzan tower; 2) the mosque roof; 3) the main prayer room (liwan); 4) the mihrab; and 5) the porch. The mathematical concepts found are number, number operation, three and two-dimensional shape, geometry transformational, and integral. Variations, according to D'Ambrosio, are counting, measuring, and classifying. The Jami' Darul Mutaqqim Mosque has elements of mathematics that can be used as a reference in the development of teaching materials in schools.